Erythropoietin Requires NF-κB and its Nuclear Translocation to Prevent Early and Late Apoptotic Neuronal Injury During β-Amyloid Toxicity - Chong, Zhao Z.; Li, Faqi; Maiese, Kenneth (Current Neurovascular Research, 2005)
No longer considered exclusive for the function of the hematopoietic system, erythropoietin (EPO) is now considered as a viable agent to address central nervous system injury in a variety of cellular systems that involve neuronal, vascular, and inflammatory cells. Yet, it remains unclear whether the protective capacity of EPO may be effective for chronic neurodegenerative disorders such as Alzheimer's disease (AD) that involve b-amyloid (Aβ) apoptotic injury to hippocampal neurons. We therefore investigated whether EPO could prevent both early and late apoptotic injury during Aβ exposure in primary hippocampal neurons and assessed potential cellular pathways responsible for this protection. Primary hippocampal neuronal injury was evaluated by trypan blue dye exclusion, DNA fragmentation, membrane phosphatidylserine (PS) exposure, and nuclear factor-κB (NF-κB) expression with subcellular translocation. We show that EPO, in a concentration specific manner, is able to prevent the loss of both apoptotic genomic DNA integrity and cellular membrane asymmetry during Aβ exposure. This blockade of Aβ generated neuronal apoptosis by EPO is both necessary and sufficient, since protection by EPO is completely abolished by co-treatment with an anti-EPO neutralizing antibody. Furthermore, neuroprotection by EPO is closely linked to the expression of NF-κB p65 by preventing the degradation of this protein by Aβ and fostering the subcellular translocation of NF-κB p65 from the cytoplasm to the nucleus to allow the initiation of an anti-apoptotic program. In addition, EPO intimately relies upon NF-κB p65 to promote neuronal survival, since gene silencing of NF-κB p65 by RNA interference removes the protective capacity of EPO during Aβ exposure. Our work illustrates that EPO is an effective entity at the neuronal cellular level against Aβ toxicity and requires the close modulation of the NF-κB p65 pathway, suggesting that either EPO or NF-κB may be used as future potential therapeutic strategies for the management of chronic neurodegenerative disorders, such as AD.
Keywords: nuclear factor- kB